Current Topics in Molecular Plant Pathology - Keiko T. Natsuaki (Jurnal Perlindungan Tanaman Indonesia, 2001)
Some current topics on molecular technology in plant pathology are reviewed. For detection and identification of plant pathogens, PCR with various modifications is applied. Study of nucleic acids sequence of pathogens gives keys for classification. For disease management, investigation of host reaction is also significant and mechanism of resistant genes is studied. In the study of plant reaction against pathogens, gene silencing is focused and compared with programmed cell death of animals. Since cost of molecular technology is still expensive, plant pathologists in Asia are expected to utilize their conventional techniques to realize ecologically sound plant protection for sustainable crop production.